Doom the politics of catastrophe - Ferguson, Niall (New York Penguin Press, 2021)
Disasters are inherently hard to predict. But when catastrophe strikes, we ought to be better prepared than the Romans were when Vesuvius erupted or medieval Italians when the Black Death struck. We have science on our side, after all. Yet the responses of many developed countries to a new pathogen from China were badly bungled. Why?
Includes bibliographical references and index.
Keywords: COVID-19 (Disease)--History.